Association of rs211037 GABRG2 gene polymorphism with susceptibility to idiopathic generalized epilepsy - Milanovska, Marija; Cvetkovska, Emilija; Panov, Sasho (My University, 2021)
Aim This case-control study aimed to determine a possible association of single nucleotide polymorphism rs211037 of the gamma-aminobutyric acid receptor subunit gamma-2 (GABRG2) gene with the susceptibility to idiopathic generalized epilepsy (IGE) in the Macedonian population. Methods It enrolled 96 patients with clinically verified IGE and 51 healthy individuals without personal and family history of epilepsy or other neurological disorders as controls. A determination of the GABRG2 rs211037 polymorphism was performed using the TaqMan-based genotyping assay. Results A significant dominant association of the CC genotype (odds ratio - OR=2.100, 95% CI=1.018-4.332; p=0.043) and allelic association of C allele (OR=1.902, CI=1.040-3.477; p=0.035) with susceptibility to IGE was found. Carriers of CC genotype had approximately a 2-fold higher probability of developing IGE than the carriers of CT and TT genotypes. Carriers of the C allele had a 1.9-folds higher probability for IGE than the carriers of the T allele. Conclusion The polymorphism rs211037 of the GABRG2 gene increases the risk of the development of idiopathic generalized epilepsy in the Macedonian population.